Malignant Peripheral Nerve Sheath Tumour of Left Vagus: A Rare Presentation in Neurofibromatosis-1 - Shivarajan, Dhamodhara Kannan; Dubhashi, Prof Dr. Siddharth P. Dubhashi; Mehra, Dr Bhupendra Mehra; Saxena, Dr Divish Saxena (International Journal of Innovative Research in Medical Science, 2024)
Background: Malignant Peripheral Nerve Sheath Tumour (MPNST) is a rare but aggressive type of soft tissue tumor. In cases associated with neurofibromatosis, where they often develop from existing plexiform neurofibromas, prognosis is poorer compared to sporadic cases. MPNST originating from a cranial nerve is extremely uncommon, requiring systematic diagnosis and surgical management based on thorough history, clinical examination, and lab tests. Case report: Our case involves a young adult male who presented with a 10 x 8 cm neck mass in the left anterior triangle, alongside other neurofibromatosis features like cafe-au-lait spots and Lisch nodules. MRI and CECT revealed a well-defined mass from the left Vagus nerve, adjacent to the left carotid artery and jugular vein. Biopsy confirmed neurofibroma, and the mass was surgically excised with negative margins, revealing MPNST upon histopathology. Conclusion: The uncommon occurrence of MPNST originating from a cranial nerve, along with its potential for local invasion and distant spread, underscores the importance of early diagnosis and prompt surgical intervention.